Developments of the electrochemical noise method (ENM) for more practical assessment of anti-corrosion coatings - Mabbutt, Stephen J.; Mills, Douglas J.; Woodcock, Christopher P. (Elsevier, 2007)
The electrochemical noise method (ENM) has particular attractions because of its non-intrusive nature, quickness in gathering data and ease of interpretation. The electrode arrangement for the standard (“Bridge”) method of conducting ENM requires two separate working electrodes, e.g. two painted Q panels and a reference electrode. Although satisfactory for laboratory use, it is not so suitable for monitoring or quality control. An improved experimental configuration is the single substrate (SS) method but this still requires the metal to be connected to the measuring instrument. This is avoided in the most recent development which needs no connection to substrate (NOCS). Results will be given for immersed low VOC samples monitored using the ENM NOCS arrangement and compared with the standard (“Bridge”) method and DC resistance. Results will also be presented for work done using several different electrodes (platinum, calomel and silver/silver chloride). It is accepted that, because of the very small voltages and currents involved, ENM data can sometimes be affected by extraneous signals (although normally the results are changed by only a factor of two or less) and it may be that NOCS is more sensitive to interference of this type than the standard bridge arrangement. A simple data analysis package checking on the Gaussian nature of data enables the operator to have confidence in the Rn value. This has been applied to NOCS data. Further work is required to make ENM attractive enough to be employed as the electrochemical method of choice by users, specifiers and producers of organic anti-corrosive paints.
Workshop on Application of Electrochemical Techniques to Organic Coatings, AETOC 2005
Keywords: Anti-corrosive coatings; Electrochemical noise method; Novel configurations; Field application